2015
DOI: 10.1111/cen.12872
|View full text |Cite
|
Sign up to set email alerts
|

The expression of microvesicles in the blood of patients withGraves' disease and its relationship to treatment

Abstract: GD patients have elevated levels of MVs that carry molecules with potential biological activities. MVs are significantly reduced after antithyroid treatment with thiamazole but still higher compared to levels in healthy controls. Assessment of MV levels and pattern may therefore provide additional information on underlying immune disturbances not obtained by measurements of hormone levels alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A previous study has shown that HMGB1 is overexpressed in the thyroid of HT patients, and HMGB1 expression is very low in healthy thyroids (44). Recent results also revealed increased numbers of HMGB1-positive monocytes in GD patients compared to healthy controls; with expression decreased by approximately 50% under antithyroid drug treatment (45). HSP60 is an intracellular chaperone that plays an important role in protein folding and stability.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that HMGB1 is overexpressed in the thyroid of HT patients, and HMGB1 expression is very low in healthy thyroids (44). Recent results also revealed increased numbers of HMGB1-positive monocytes in GD patients compared to healthy controls; with expression decreased by approximately 50% under antithyroid drug treatment (45). HSP60 is an intracellular chaperone that plays an important role in protein folding and stability.…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmunity, platelet EVs seem to influence the course of disease, being present in high levels in patients with RA (9698), SLE (98, 99), Grave's disease (100) and systemic sclerosis (101). In RA, EVs can act through several different pathways, presenting antigens to the immune system, degrading extracellular matrix, carrying miRNA and autoantigens, such as citrullinated proteins, resulting in induction of inflammation, as well as perpetuating it by formation of bioactive immunocomplexes (ICs) (23, 98).…”
Section: Hmbg1 and Autoimmunitymentioning
confidence: 99%
“…Microvesicles are released into the circulation from multiple cell types during apoptosis and reflect metabolic stress. A very recent case–control study from Sweden investigated the number of microvesicles (i.e., diameter < 1 μm) in the blood of patients with GD, which was seen to be increased in the blood of GD patients compared with healthy controls and to remain elevated after medical therapy, albeit at a lower level [ 80 ]. This concept might as well offer a new biomarker to guide future treatment decisions in patients with GD.…”
Section: Main Textmentioning
confidence: 99%